Functional Group Analysis and Optical Properties of Oyster Mushroom’s Mycelium Using Sorghum Media with FTIR Spectrophotometer - Nazopatul Patonah Har; Lusia Anita Br. Sagala; Mohammad Nuzaihan Md Nor; Irzaman, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
The successful establishment of oyster mushroom seeds depends on Potato Dextrose Agar (PDA). In this study, the sterilization level of media varied from level 1 to 3. For each sterilization level, PDA was steamed at 102 oC for 60 minutes. The best result was observed at the third level, as indicated by mycelial growth. All the spreads (F1) were good and non-tampered with. The result of growing the spread seeds by using sorghum media was not contaminated. The characterization result of FTIR mycelium from pure culture (F0), spread seeds (F1), and planting seeds (F2) indicated the stretching vibration. Stretching vibration showed several functional groups. They were C-O, C-N, C=O, C-H, O-H, and β-D-glukan. These results suggest that the energy required for mycelium growth in the spread seedling culture media is smaller than that required for planting seedling culture media. This follows from the relationship between photon energy and wavenumber, which is directly proportional. The LO values are at wavenumbers 590 cm-1 and 905 cm-1 for each of the samples F0 and F1. While the TO value is at wave numbers 577 cm-1 and 850 cm-1 for each sample F0 and F1.